Analisis Perbandingan Aplikasi Program Microsoft Project Dan Metode Cpm Dalam Penjadawalan Proyek Konstruksi - Faathir thaariq faathir (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2024)
Ganesha Hotel problems can affect the delay of a project. Often the project delays will be very expensive, good value. viewed from the contractor's and owner's side. In order to avoid incurring implementation time and costs, it is necessary to carry out project scheduling so that research on project completion time to avoid problems using the existing critical path method and MS Project scheduling will be very useful in project development. the relationship between one activity and other activities and the entire project, identifying activities that must be prioritized, the benefits of the critical path method is knowing the critical path, delays in project activities on the critical path will automatically hinder all project activities, and this Microsoft Office Project MS Project tool for more efficient projects and project portfolio management, the most frequently used for MS Project for construction projects are the main modules of MS Project including project work and project teams. This MS Project makes it easier to create construction schedules, create Wed prices This research is a descriptive analysis, namely describing the condition of the construction of the Ganesha Hotel by collecting data from the project using this method to analyze the efficiency, time and cost of research using the Ms Project application and the Critical Path Method. The prediction results for each segment are compared to make a comparison to find out which work needs to be done. comes first and work that doesn't need to come first. From the research carried out, it can be concluded that in the research process using Ms Project, the results were that the completion time was 189 days from the project plan of 210 days, so there was a time efficiency of 21 days, whereas in the research using CPM, the results were that the completion time was 188 days from the project plan of 210 days, so there were efficiency 22 days From the research we conducted to compare the time of Ms Project and Critical Path Method there is a difference of one day while for the costs obtained from comparing the 2 methods IDR 26,426,500,000